METODE BRACKETING EDMUN HUSSERL - Syamsul Amal (DIALEKTIKA, 2019)
ABSTRACT This article intends to put forward the views phenomenology of Edmund Husserl, by using methods of desecaraiptive analysis of the data obtained in writing either of journals, books and articles obtained from the website, and blog. This study found that, first, intentional awareness is directed to the object that appears or appeared, without intentional object does not mean anything, and vice versa. Second, epoche or bracketing is the method used so that researchers can obtain the original data, by actively participating live the experience along with the living world, then did the reduction or containment or delay of assumptions, theories, knowledge, and even beliefs that may hamper researchers obtained data pure, by letting the objects speak for themselves. (Zurruk zu den zahen selbst). Religion is a manifestation of one's beliefs, to find out the essence of religious teachings that were understood then the method of bracketing is definite. Keywords: phenomenology, Edmund Husserl, intentional, bracketing